Desempenho de vacas leiteiras em pastagens de capim estrela africana sob doses crescentes de nitrogênio - Almeida, Flebson Montalvão de (2014)
This research was carried out in order to evaluate forage mass, its chemical composition and intake, milk yield per cow and per area, milk composition and the metabo lic profile of stargrass pasture under increasing nitrogen doses. Treatments were 0, 200, 400 e 600 kg/ha/year using urea as nitrogen source. A randomized block design with two replications was used. Lactating Holstein x Zebu cows were blocked by milk prod uction , lactation number, liveweight and by genetic group, using six cows per hectare in the start of the experiment. Daily cows were fed with 2 kg/ cow of a concentrate with 20% Crude Protein (CP) and 70% Total Digestible Nutrients , during the experiment. Forage mass was estimated before and after grazing and intake by the difference between forage mass on offer and remaining residual forage in all grazing cycles. CP, neutral detergent fiber ( NDF ) and in vitro dry matter digestibility (IVDMD) contents wer e analyzed by a NIRS Spectofotometer. Milk production was evaluated at each seven days and m ilk composition at each grazing cycle. Milk yield per area was calculated by multiplying the average daily milk yield per cow and its respective average car rying ca pacity rate for each treatment. Results showed that there is an augment on forage mass as of increasing nitrogen doses, with greatest yields from 200 kg/ha/year of N. As far increasing N doses there are augments on CP and IVDMD and decreasing on NDF conten ts. However, there are no effects on dry matter intake, milk yield per cow and to milk composition, but there is influence upon animal production per hectare and the greatest values occur between 200 and 600 kg/ha/year of N. There are decreasing on ß - hydroxybutyrate , non - esterified fatty acids and triglycerides values with increasing in N doses, and increasing the urea values from 200 kg/ha/year of N, but no effect over cholesterol and mineral contents were observed.